Hypofibrinolytic state and high thrombin generation may play a major role in SARS‐COV2 associated thrombosis. (11th August 2020) - Nougier, Christophe; Benoit, Remi; Simon, Marie; Desmurs‐Clavel, Helene; Marcotte, Guillaume; Argaud, Laurent; David, Jean Stephane; Bonnet, Aurelie; Negrier, Claude; Dargaud, Yesim
Abstract: Background: Thirty percent of Covid‐19 patients admitted to intensive care units present with thrombotic complications despite thromboprophylaxis. Bed rest, obesity, hypoxia, coagulopathy, and acute excessive inflammation are potential mechanisms reported by previous studies. Better understanding of the underlying mechanisms leading to thrombosis is crucial for developing more appropriate prophylaxis and treatment strategies. Objective: We aimed to assess fibrinolytic activity and thrombin generation in 78 Covid‐19 patients. Patients and Methods: Forty‐eight patients admitted to the intensive care unit and 30 patients admitted to the internal medicine department were included in the study. All patients received thromboprophylaxis. We measured fibrinolytic parameters (tissue plasminogen activator, PAI‐1, thrombin activatable fibrinolysis inhibitor, alpha2 anti‐plasmin, and tissue plasminogen activator‐modified ROTEM device), thrombin generation, and other coagulation tests (D‐dimer, fibrinogen, factor VIII, antithrombin). Results and Conclusions: We observed two key findings: a high thrombin generation capacity that remained within normal values despite heparin therapy and a hypofibrinolysis mainly associated with increased PAI‐1 levels. A modified ROTEM is able to detect both hypercoagulability and hypofibrinolysis simultaneously in Covid‐19 patients with thrombosis.